Challenges in diagnosing cardiac sarcoidosis: should we increase our index of suspicion? - Ariana Rose Tagliaferri (Greater Baltimore Medical Center, 2020)
Sarcoidosis is a multisystem disease involving the lungs in up to 90% of cases; however, 30% of patients will have systemic sarcoidosis, including involvement of the heart. Cardiac sarcoidosis can affect any part of the heart and manifest in various ways, with the most common presentations being AV block, arrhythmias, heart failure and sudden cardiac death. Due to the overlap of symptoms and other cardiac diseases, including silent disease, cardiac sarcoidosis is difficult to diagnose. Many cases are underreported. However, due to the nature of the disease, cardiac sarcoidosis can have serious consequences that can be prevented with early intervention. This paper will focus on the challenges in diagnosing cardiac sarcoidosis, how to differentiate cardiac sarcoidosis from other common conditions by detecting subtle clinical differences, and how various investigations and imaging modalities should be used in aiding diagnosis and determining prognostic severity, such that early intervention can be initiated.